2021
DOI: 10.1175/jhm-d-20-0283.1
|View full text |Cite
|
Sign up to set email alerts
|

Wintertime precipitation over the Australian Snowy Mountains: Observations from an Intensive Field Campaign 2018

Abstract: Understanding the key dynamical and microphysical mechanisms driving precipitation in the Snowy Mountains region of southeast Australia, including the role of orography, can help improve precipitation forecasts, which is of great value for efficient water management. An intensive observation campaign was carried out during the 2018 austral winter, providing a comprehensive range of ground-based observations across the Snowy Mountains. We used data from three vertically pointing rain radars, cloud radar, a PARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 33 publications
(33 reference statements)
1
15
0
Order By: Relevance
“…Maahn and Kollias (2012) developed an algorithm to improve the sensitivity of the older MRR-2 instrument from a minimum of 3 dBZ to −10 dBZ, allowing for a much improved detection of snowfall. We implemented a modified version of the Maahn and Kollias (2012) code for our MRR-PRO instrument, using the method developed by Ackermann et al (2021).…”
Section: Micro Rain Radarmentioning
confidence: 99%
See 1 more Smart Citation
“…Maahn and Kollias (2012) developed an algorithm to improve the sensitivity of the older MRR-2 instrument from a minimum of 3 dBZ to −10 dBZ, allowing for a much improved detection of snowfall. We implemented a modified version of the Maahn and Kollias (2012) code for our MRR-PRO instrument, using the method developed by Ackermann et al (2021).…”
Section: Micro Rain Radarmentioning
confidence: 99%
“…We implemented a modified version of the Maahn and Kollias (2012) code for our MRR‐PRO instrument, using the method developed by Ackermann et al. (2021).…”
Section: Data and Analysismentioning
confidence: 99%
“…Air masses arriving from the Southern Ocean are often highly pristine before they cross into southeastern Australia (Huang et al, 2017, 2021), featuring few ice‐nucleating particles (INP, McCluskey et al, 2018). These weather systems are renowned for favoring the generation of supercooled liquid water (SLW)‐topped clouds across high‐elevation regions of southeastern Australia and Tasmania, when the pristine postfrontal maritime air mass brings moisture from the Southern Ocean and encounters the orographic barriers (Ackermann et al, 2021; Chubb et al, 2012; Morrison et al, 2013; Osburn et al, 2016). Cloud microphysical processes associated with those postfrontal clouds and precipitation have been considered by previous observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…Cloud microphysical processes associated with those postfrontal clouds and precipitation have been considered by previous observational studies. In particular, observations from a 2018 ASM wintertime intensive field campaign showed that the postfrontal clouds precipitate primarily due to riming processes (Ackermann et al, 2021). Prolonged precipitation events were mostly associated with stratiform ascent, while the cloud thickness and precipitation intensity were highly sensitive to the potential blocking and stability of the low‐level upstream flow (Ackermann et al, 2021; Manton et al, 2017; Sarmadi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation